Lipase Enzyme Kinetics with the Addition of Avocado Seed Extract as an Inhibitor in Olive Oil - Maudiyanti, Raras; Herdyastuti, Nuniek (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2024)
Free fatty acids are compounds resulting from the hydrolysis of triglycerides catalyzed by the enzyme lipase. Free fatty acids harm health if they enter the body in large amounts. Avocado seed extract can reduce free fatty acid levels by inhibiting lipase activity. This research is a type of true-experimental research that aims to determine the effect of variations in substrate concentration on lipase enzyme activity with the addition of avocado seed extract and to determine the impact of the addition of avocado seed extract as an inhibitor on lipase enzyme kinetics. Lipase activity was determined based on the amount of oleic acid formed using Cu acetate pyridine reagent by Uv-Vis spectrophotometry at a wavelength of 715 nm. Lipase enzyme kinetics were determined using the Lineweaver-Burk curve equation, a transformed form of the Michaelis-Menten equation. The results showed that 60% substrate concentration was the most effective in reducing lipase enzyme activity by 60%. In addition, the addition of avocado seed extract proved to act as a competitive inhibitor, with the KM value decreasing from 0.014 M to 0.004 M and Vmaks remaining relatively stable at 23.2 µM. This shows that avocado seed extract effectively reduces lipase enzyme activity, which has implications for reducing FFA levels in olive oil. Thus, this study concludes that avocado seed extract has great potential as a natural inhibitor agent in reducing lipase enzyme activity.